Good Samaritan mini: urban search and rescue robot - Hoover, Nathaniel David, author; Haygood, Nicholas John, author; Guthrie, Brian D., author; Bernstein, Ian H., author; Rector, Michael Holman, author; Maciejewski, Anthony A., author (Colorado State University. Libraries, 2006)
In the wake of disasters such as the 9/11 attacks, it becomes clear that immediate rescue efforts must take place in a way that doesn't put the lives of the rescue workers themselves at stake. It is situations like these where urban search and rescue robots (USARs) can save lives while keeping rescue workers safe. Over the past few years, Engineers at Colorado State University have been developing a USAR platform dubbed "Good Samaritan (GS)," for the RoboCup USAR Competition. This competition presents mock building collapses to competitors in an attempt to advance robotics technology towards eventual real-world use. GS Mini is the latest iteration in the GS series and offers a platform size that is roughly half that of the 2005/2006 design. By analyzing the current GS design, and Pro/E structural analysis, our team has come up with a solution to reduce the overall size of the robot while maintaining as many features of the larger platform as possible. This allows it to access harder to reach victims in more confined spaces. Over the next six months our team will be constructing the GS Mini platform from our design and competing in the 2007 RoboCup competition.
Keywords: RoboCup; USARs; USAR; urban search and rescue robot; GS; Good Samaritan; robots; robotics